Laporan Kasus: Tantangan Pengelolaan Krisis Hiperglikemia Pasien Penyakit Ginjal Kronik (PGK) Tahap Akhir dalam Hemodialisa Rutin - Davin Takaryanto; Maya Kusumawati; Nenny Agustanti; Rudi Supriyadi; Ervita Ritonga; Nanny N. M. Soetedjo; Hikmat Permana (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Introduction Hyperglycemic crisis is a life threatening medical emergency which occur in any individuals, including end stage renal disease (ESRD). The altered renal, glucose, electrolyte, and body fluid dysregulation seen in ESRD patients affects the management. Objective: Hyperosmolar hyperglycemic state (HHS) and diabetic ketoacidosis (DKA) are life threatening hyperglycemic emergencies that warrant immediate and adequate management. The incidence of hyperglycemic crises among ESRD patients who undergo routine hemodialysis remains unknown. Furthermore, several available studies reported in case reports. Methods: We hereby report a case of hyperglycemic crisis of 61years old woman with medical history of type 2 diabetes mellitus (DM) and ESRD as the complication, she undergoes routine hemodialysis. Results: The patient was admitted with decreased consciousness that was preceded by dyspnea, active cough and fever. Then, the patient treated for the hyperglycemic crisis as in ESRD patient and for the with septic shock due to pneumonia. Conclusion: The management of hyperglycemic crises consist of fluid, potasium corection and insulin administration, however there were some adjustment in ESRD patients. At present therere were no spesific guidelines to manage hyperglicemic crisis and ESRD which is challenging.